Analysis Size Company and Size Public Accountant Firm on Audit Quality with Time Budget Pressure As a Moderating Variable - Nida Fitria Nurani Putri Majid; Merlyana Dwinda Yanthi (Jurnal Akuntansi, 2025)
This study aims to analyze the effect of company size , size of the Public Accounting Firm (KAP) on audit quality by considering time budget pressure as a moderator. The population data used is all mining companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. This study used a purposive sampling method and obtained a sample of 228 companies . The data was analyzed using moderation regression analysis (MRA). The results showed that the size of the Public Accounting Firm (KAP) has a positive effect on audit quality , while company size has no effect on audit quality . In addition , time budget pressure cannot moderate the effect between company size and Public Accounting Firm (KAP) size on audit quality .